Characterization of Zinc and Cadmium Hyperaccumulation in Three Noccaea (Brassicaceae) Populations from Non-metalliferous Sites in the Eastern Pyrenees - Martos, Soledad; Gallego, Berta; Sáez, Llorenç; López-Alvarado, Javier; Cabot, Catalina; Poschenrieder, Charlotte (Frontiers in Plant Science, 2016)
The Southern slope of the Pyrenees is the meridional limit for the distribution of Noccaea populations. However, the systematic description of these populations and their hyperaccumulation mechanisms are not well established. Morphological and genetic analysis (ITS and 3 chloroplast regions) were used to identify Noccaea populations localized on non-metallicolous soils during a survey in the Catalonian Pyrenees. Cd and Zn concentrations were analysed in soils and plants both sampled in the field and grown hydroponically. The expression of selected metal transporter genes was assessed by quantitative PCR. The populations were identified as Noccaea brachypetala (Jord.) F.K. Mey by conspicuous morphological traits. Principal component analysis provided a clear separation among N. brachypetala, Noccaea caerulescens J. & C. Presl and Noccaea occitanica (Jord.) F.K. Mey., three Noccaea species reported in the Pyrenees. Contrastingly, ITS and cpDNA analyses were unable to clearly differentiate these taxa. Differences in the expression of the metal transporter genes HMA3, HMA4, and MTP1 between N. caerulescens and N. brachypetala, and those amongst the N. brachypetala populations suggest differences in the strategies for handling enhanced Cd and Zn availability. This is the first report demonstrating Cd and Zn hyperaccumulation by N. brachypetala both in the field and in hydroponics. This comprehensive study based on taxonomic, molecular, and physiological data allows both the correct identification of this species and the characterization of population differences in hyperaccumulation and tolerance of Zn and Cd.